2004
DOI: 10.1161/01.cir.0000143378.58099.8c
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Systemic Endothelial Dysfunction in Patients With Acute Coronary Syndromes

Abstract: Background-Endothelial vasodilator dysfunction may serve as a marker integrating the vascular risk of an individual; however, whether systemic vasodilator function predicts disease progression and cardiovascular event rates in patients with manifest acute coronary syndromes (ACS) is unknown. Methods and Results-In 198 patients with angiographically documented ACS, forearm blood flow (FBF) responses to acetylcholine (ACH; 10 to 50 g/min) and sodium nitroprusside (SNP; 2 to 8 g/min) were measured by venous occlu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
100
0
4

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 241 publications
(107 citation statements)
references
References 47 publications
3
100
0
4
Order By: Relevance
“…Although median homoarginine concentrations were not significantly different between ACS and NCCP patients, the predictive value of low homoarginine on incident MACE—in the overall study population as well as in the subsample of ACS patients—was evident. It is generally accepted that atherosclerosis plays a pivotal role in pathogenesis of ACS 7, 8. In line with this, Valtonen et al.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Although median homoarginine concentrations were not significantly different between ACS and NCCP patients, the predictive value of low homoarginine on incident MACE—in the overall study population as well as in the subsample of ACS patients—was evident. It is generally accepted that atherosclerosis plays a pivotal role in pathogenesis of ACS 7, 8. In line with this, Valtonen et al.…”
Section: Discussionmentioning
confidence: 78%
“…Onset of an acute coronary syndrome (ACS) is related to plaque instability and subsequent inflammation, coronary thrombosis, and/or vasospasms. The link between endothelial dysfunction and ACS is thus not direct, but peripheral endothelial function testing predicts cardiovascular outcome in ACS, and subsequent normalization of endothelial function in these patients lowers event rates 7, 8…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that endothelial function can be modified by interventions including aerobic exercise, body weight reduction, and pharmacological therapy 2. Several investigators have shown that repeated assessment of vascular function has much greater predictive power of cardiovascular disease progression and cardiovascular outcomes 26, 27. Repeated measurement of ezFMD will enable specific conclusions concerning the role of ezFMD in future cardiovascular events to be drawn.…”
Section: Discussionmentioning
confidence: 99%
“…59 Despite these limitations, venous occlusion plethysmography predicted cardiovascular events. 47,48,50,54 Pulse waveform analysis/peripheral arterial applanation tonometry Applanation tonometry was originally designed to measure intraocular pressure, but has been adapted to measure arterial pulse (pressure) waveforms. The tonometer, a device resembling a short pencil, is positioned over the radial artery maximal pulsation to minimally flatten the arterial wall.…”
Section: Venous Occlusion Plethysmographymentioning
confidence: 99%